DAMPAK KELUARGA TAK UTUH PADA PERKEMBANGAN PSIKOLOGIS ANAK - Ferent Ahda Awalia; Imaniar Purbasari; Ika Oktavianti (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses a study regarding the condition of a broken home family on the parents’ role in education, needs, social, and character-building of children and the impact of a broken home. The formulation of the problem of broken homes comes from broken home family conditions in Terkesi Klambu, Grobogan and the impact of a broken home in Terkesi Klambu, Grobogan. The study used a qualitative descriptive method as a research design stage in conducting the study. The study was conducted in Terkesi Klambu, Grobogan. The study also involved parents and children as the research subjects. This study used data collection techniques that included the stages of observation, in-depth interviews, documentation, and recording. The data analysis used was interactive data analysis. The results of the analysis showed that the condition of the broken home family in Terkesi Klambu Grobogan was different. Some were still good, and some were not dependent on the level of parents’ wareness who played a role to fulfill the children’s needs. In addition, the broken home family has an impact on the psychological development of children.